Kajian Awal Pemanfaatan Rumput Teki (Fimbristylis sp), Linggi (Penicum sp) dan Sianik (Carex sp) sebagai Serat Alami untuk Bahan Alat Penangkapan Ikan - Nofrizal, Nofrizal; Ahmad, Muchtar; Syofyan, Irwandy; Habibie, Ied (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
This research was aimed to study about the potential of fiber structure teki grass (Fimbristylis sp), linggi grass (Penicum sp) and sianik grass(Carex sp) as natural fibre for fishing gear materials. The parameter of this research are; water content, elongation, breaking strength andhistology of the fiber. This research used the observation and experimental method. The observation method is used to know the fiberstructure and water content of teki grass, linggi grass and sianik grass. The experimental method was used to test the breaking strength andelongation of the objects in wet and dry condition. Based on the histology observation, teki grass has an epidermis layers as fiber structure.It consists of parenchyma tissue and collenchymas tissue.Fiber structure of linggi grass and sianik grass are similar with teki grass. Sianikgrass has the most excessive epidermis layer than others i.e. 5.57 gram. The average water content of teki grass is 1.03 gram, and linggi grassis 0.17 gram. Based on the breaking strength test, sianik grass is stronger than others with average strength 9.05 kgf in wet condition and9.75 kgf in dry condition. Meanwhile, breaking strength of the teki grass and linggi grass is 3.20 kgf and 4.16 kgf in wet condition and 4.30kgf and 5.25 kgf in dry condition. The average of the elongation of sianik grass is longer than others i.e. 24.50 mm in wet condition and18.75 mm in dry condition. The elongation of teki grass is 9.05 mm in wet condition and 11.10 in dry condition. The average of linggi grasselongation is 12.20 mm in wet condition and 12.90 mm in dry condition. Based on the breaking strength and the elongation test, the resultshowed that sianik grass is the most potential natural fiber as fishing gear material.